2021
DOI: 10.1051/shsconf/20219601010
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Efficiency and Potential of China's Trade with South Asian Countries-Based on the Stochastic Frontier Gravity Model

Abstract: In the context of COVID-19, international trade has been strongly impacted, and it is of great significance to accelerate trade exchanges with countries along the "Belt and Road" to achieve trade transformation. This paper uses the time-varying stochastic frontier gravity model to measure trade efficiency based on the data of China and South Asia from 2000 to 2019. The empirical results show that economic scale and population have a positive impact on trade. China's GDP growth is not conducive to the growth of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Wang Ling etc. [3] (2019) measured the trade efficiency and trade potential of the Bangladesh-China-India-Myanmar Economic Corridor using a stochastic frontier gravity model and estimated the main factors affecting the trade volume, and the results showed that China and India have great trade potential, and efficient economic and trade cooperation would drive the development of the entire Bangladesh-China-India-Myanmar region and produce huge economic effects. Currently, the literature related to the study of trade potential between India and China exists mainly for products such as electronic mechanics.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Wang Ling etc. [3] (2019) measured the trade efficiency and trade potential of the Bangladesh-China-India-Myanmar Economic Corridor using a stochastic frontier gravity model and estimated the main factors affecting the trade volume, and the results showed that China and India have great trade potential, and efficient economic and trade cooperation would drive the development of the entire Bangladesh-China-India-Myanmar region and produce huge economic effects. Currently, the literature related to the study of trade potential between India and China exists mainly for products such as electronic mechanics.…”
Section: Review Of the Literaturementioning
confidence: 99%